Influence of helicobacter pylori infection on Chinese adult males’ body muscle mass: a cross-sectional and cohort analysis - Liu, Ju-Hua; Li, Yun; Nie, Rui-Ning; Li, Jun-Xiang; Cheng, Fang-Yuan; Su, Yu-Xin; Yang, Yun-Feng; Gu, Jian-Wei (Frontiers in Cellular and Infection Microbiology, 2025)
AimHelicobacter pylori (HP) infection may cause many disorders outside the digestive system, although research on the association between HP infection and muscular atrophy among males is limited. This study aimed to examine the influence of HP infection on adult Chinese males’ body muscle mass using a cross-sectional and cohort analysis.MethodsA total of 8110 Chinese adult males were enrolled in the study. HP infection was assessed using the C13 breath test. Using bioelectrical impedance analysis (BIA), body muscle mass was detected and total muscle mass, total skeletal muscle mass, and appendicular skeletal muscle mass index (ASMI) were recorded. Univariate and multivariate linear regression analyses were conducted to identify the factors associated with body muscle mass.ResultsSubjects with HP infection had a lower total muscle mass, total skeletal muscle mass, and ASMI compared with those without HP infection (P < 0.01). Univariate and multivariate linear regression analyses demonstrated that HP infection was an independent risk factor of total muscle mass, total skeletal muscle mass, and ASMI (P < 0.01); this association persisted when subjects were divided into young, middle-aged, and elderly according to age (P < 0.01). A subsequent cohort study confirmed that persistent HP infection accelerated the pathological process of muscle decline (P < 0.01).ConclusionHP infection is an independent risk factor for muscle decline in adult Chinese males, long-term HP infection may accelerate this pathological progression.